Effects of climate change on future extreme rainfall indices over Thailand - S. Maijandee (2018)
Extreme rainfall indices were calculated based on daily rainfall data derived from the outputs of MM5-RCM simulations. Projected changes of these indices in the future (2020s) under the IPCC Special Report on Emissions Scenarios (SRES) A1B compared to the reference period (1990s) were analyzed. Before calculating the indices, the raw outputs from the MM5-RCM were adjusted in order to reduce biases as part of the bias-correction process. The validation demonstrates that the average and cycle of annual rainfall in the reference period are reproduced reasonably in the bias-corrected MM5-RCM results. The projected changes of the rainfall indices suggest that in the future most areas of northern, western, and northeastern Thailand will become wetter in the wet season and drier in the dry season. Central and eastern Thailand will become drier in the wet season while in the dry season rainfall will become more intense, and rainy days will become more scattered with a higher number of heavy rainfall days. In the south, the length of the wet spell will be decreased in the Southern Andaman Sea area and increased in East-Southern Region. The dry spell will likely be shorter throughout the southern region for all seasons. © 2014 Global NEST Printed in Greece. All rights reserved.